Vasovagal reactions among blood donors in tertiary hospital Kathmandu. - Shakya, Aman (2021)
ABSTRACT: Introduction: Demand of blood and blood products is high and supply is inadequate. Blood is resourced from healthy donors. Generally blood donation is well tolerated but few experience adverse reactions. Adverse reactions are mostly vasovagal reactions which can have negative impact on donor return. Clinically, vasovagal reaction is unpleasant feeling of weakness, dizziness, sweating, pallor, nausea, vomiting, convulsion and even loss of consciousness. Pathophysiologically, vasovagal reaction involve both vasodilation and bradycardia. Prevalence of vasovagal reaction has been studied in different parts of world at different times that ranges from 0.87% to 13%. There are various predictors for vasovagal reaction like young age, female gender, first time donors, replacement donors, low body weight, low blood pressure before donation and low pulse rate before donation. Objective of the Study: The study was carried out to estimate the frequency of vasovagal reactions among the blood donors in blood bank of a tertiary hospital, Kathmandu. Research Design and Methodology: This was an observational cross sectional study conducted to estimate the frequency of vasovagal reactions among blood donors in blood bank of Tribhuvan University Teaching Hospital, Kathmandu from December 2020 till April 2021. In this study, 180 donors who were eligible to donate blood were included. Baseline heart rate, systolic and diastolic blood pressure were recorded. The heart rate and blood pressure were noted again during donation, immediately after needle removal and five minutes after donation. After donation the symptoms of vasovagal reaction were also noted. Frequency of vasovagal reaction was calculated among 180 donors. Change in heart rate and blood pressure during, immediately after and after five minutes of donation was compared using paired t test with the baseline heart rate and blood pressure. Results: Out of 180 donors, seven donors experienced vasovagal reaction. Mean age of donors was 30.76±9.15 years. Baseline mean heart rate was 78.18±8.47 beats per minute which dropped to 72.95±9.30 beats per minute (p value < 0.001) during donation. Immediately after donation mean heart rate further dropped to 71.76±9.56 beats per minute (p value < 0.001). After five minutes of donation mean heart rate became 72.92±8.89 beats per minute (p value < 0.001). Similarly baseline mean systolic blood pressure was 125.20±10.59 mm Hg which dropped to 117.57±13.43 mm Hg (p value < 0.001) during donation. Immediately after donation mean systolic blood pressure further decreased to 113.06±13.99 mm Hg (p value < 0.001). After five minutes of donation mean systolic blood pressure became 113.76±11.91 mm Hg (p value < 0.001). Baseline mean diastolic blood pressure was 81.97±7.20 mm Hg which decreased to 77.79±10.36 mm Hg (p value < 0.001). Immediately after donation mean diastolic blood pressure further decreased to 74.83±11.43 mm Hg (p value < 0.001). After five minutes of donation mean diastolic blood pressure became 76.63±9.77 mm Hg (p value < 0.001). Conclusion: Vasovagal reaction rate of 3.88% was seen in this study among the donors visiting blood bank of TUTH, Kathmandu. There was highly significant drop in heart rate during donation, immediately after donation and after five minutes of donation. The decrease in systolic blood pressure was highly significant during, immediately after and after five minutes of donation. Diastolic blood pressure also decreased which was highly significant during, immediately after and after five minutes of donation. Keywords: Blood donors, blood pressure, heart rate, vasovagal reaction